Thermochronological insights into the morphotectonic evolution of the Eastern Highlands, Zimbabwe: Implications for thermal history modelling of multi-thermochronometer data. (October 2019) - Mackintosh, Vhairi; Kohn, Barry; Gleadow, Andrew; Belton, David X.
Abstract: The Eastern Highlands form a north-south trending high relief region along the eastern border of Zimbabwe, which is also spatially coincident with the eastern Zimbabwe cratonic margin. Uncertainty surrounds when this mountain range formed and how the region has evolved, particularly as there are no Phanerozoic cover rocks preserved. Here, we use low-temperature thermochronology (apatite fission track, apatite (U–Th-Sm)/He and zircon (U–Th)/He dating) and inverse thermal history modelling to reveal the morphotectonic evolution of this region since the mid-Paleozoic. The data suggest that structural reactivation occurred in the Late Devonian and Jurassic-Cretaceous that caused tectonic denudation and crustal cooling in the northern Eastern Highlands. The first period is thought to be associated with post-orogenic extension following Pan-African activity. The ensuing denudation continued into the Triassic and substantiates previous suggestions that these mountains were a source region of Lower Karoo sediments. The Jurassic-Cretaceous episodes are most likely associated with stress transmission from the progressive breakup of Gondwana. These events include the mid-to Late Cretaceous reactivation of the Mutare Shear Zone, which caused upward displacement (∼800 m) of the southern Eastern Highlands. The Eastern Highlands then entered a relatively quiescent phase with all samples residing close to the surface (<60 °C) since at least the beginning of the Cenozoic, which limits subsequent denudation of these mountains to less than ∼3 km. An investigation of the different multi-thermochronometer modelling combinations reinforces concerns with the current zircon radiation damage accumulation and annealing model (ZRDAAM). However, the findings also suggest that presenting the observed versus predicted apatite fission track length distribution should be an essential reporting requirement for thermal history modelling. Highlights: Post-Pan-African orogenic extension triggered tectonic denudation in Late Devonian. Jurassic-Cretaceous denudation related to Gondwana breakup stress transmission. Eastern Highlands potential major Lower Karoo source region for West Gondwana. Comparison of observed vs model-predicted track length distribution essential.